1958
DOI: 10.1037/h0049093
|View full text |Cite
|
Sign up to set email alerts
|

Retention in Paramecium aurelia.

Abstract: Having elicited from the protozoan, Paramedwn a-urelia, behavior which seemed not unlike associative learning in higher organisms (3), we have been trying to discover what internal mechanism(s) might underlie such a surprising finding. During certain fertilization processes, the nuclei of single animals undergo disintegration and restructuring. Yet, acquisition seemed not to be adversely affected (6) by such ongoing drastic internal reorganization when tests of performance were administered immediately after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Other relatively recent experiments that have dealt with this issue are those of Gelber (1952Gelber ( , 1956Gelber ( , 1957Gelber ( , 1958Gelber ( , 1962aGelber ( , 1962b, Jensen (1957aJensen ( , 1957b, and Katz and Deterline (1958). Gelber reported successful conditioned approach behavior to a sterile platinum wire inserted into a reservoir containing paramecia after the paramecia had received training with the wire coated with food (bacteria).…”
mentioning
confidence: 99%
“…Other relatively recent experiments that have dealt with this issue are those of Gelber (1952Gelber ( , 1956Gelber ( , 1957Gelber ( , 1958Gelber ( , 1962aGelber ( , 1962b, Jensen (1957aJensen ( , 1957b, and Katz and Deterline (1958). Gelber reported successful conditioned approach behavior to a sterile platinum wire inserted into a reservoir containing paramecia after the paramecia had received training with the wire coated with food (bacteria).…”
mentioning
confidence: 99%
“…Based on the previous research into paramecia"s retention capabilities completed by Gelber (1958), Huber et al (1974), and Hennessey et al (1979) it was expected that paramecia would remember a learned task for a retention interval of several minutes. However, analysis of the data suggests that if a retention interval exists in paramecium it is less than 1 min long.…”
Section: Discussionmentioning
confidence: 99%
“…Gelber (1958) looked at retention in paramecia using the previously discussed procedure and found retention in paramecia to last three hours. Because of the previously mentioned potential flaws in the experimental design the "retention" may not have been the result of a learned behavior.…”
mentioning
confidence: 99%
“…Some studies have also shown that an organism like paramecium demonstrates the capability of learning through repetitive conscious behaviour (Gelber, 1958). These organisms have no synapses or neural networks and hence they rely on their cytoskeleton for sensation, locomotion and information processing.…”
Section: Were Primitive Organisms Conscious?mentioning
confidence: 99%
“…Some studies have also shown that an organism like paramecium demonstrates the capability of learning through repetitive conscious behaviour (Gelber, 1958). Amoeba also searches its food by moving on pseudopods toward its prey that they eventually surround, engulf and digest.…”
Section: Consciousness In Biologymentioning
confidence: 99%